Promising behavior change techniques for climate-friendly behavior change – a systematic review - Masciangelo, Lisa; Lopez Lumbi, Susanne; Rinderhagen, Michel; Hornberg, Claudia; Liebig-Gonglach, Michaela; Mc Call, Timothy (Frontiers in Public Health, 2024)
Besides societal and governmental actions to mitigate greenhouse gases, individual behavioral 28 changes are also urgently needed to limit global temperature rise. However, these individual 29 changes have proven to be difficult to achieve in the general population. We conducted a 30 systematic review in five electronic databases with the aim of systematically depicting the 31 content of interventions that promote climate-friendly behavior in individuals and households 32 in high- and upper-middle-income countries. We included 25 studies. The analyses included 33 identification of the used Behavior Change Techniques (BCTs) and comparison of their promise 34 ratio. Across our three outcome categories energy consumption, water consumption, and 35 mobility the most frequently used BCT categories are not the ones that are most promising in 36 terms of behavior change. Based on these results, our recommendation for climate change 37 mitigation interventions is to include components that provide concrete instructions on how to 38 perform the desired behavior (shaping knowledge), setting goals and commitments (goals and 39 planning), substituting undesired behavior, and practicing desired behavior (repetition and 40 substitution). Other reviews with similar aims use different wordings, definitions, or degrees of 41 detail in their intervention component labelling which makes it difficult to compare the results. 42 We recommend to use a standardized classification system, like the BCT taxonomy in 43 combination with the promise ratio, which this study has shown to be a suitable tool to classify 44 applied intervention techniques and give an indication of successful techniques.